333 SOUNDCLOUD SEBAGAI MEDIA ALTERNATIF DISTRIBUSI KARYA MUSIK MUSISI INDIE KOTA MAKASSAR - Andi Muhammad Fauzi Ramadhan; Sudirman Karnay; Andi Subhan Amir (KAREBA : Jurnal Ilmu Komunikasi, 2017)
ABSTRACT The purpose of this research is: (1) To find motive of indie musicians on using Soundcloud as an alternative media distribution for musical pieces. (2) To find effort of indie musicians on using Soundcloud as an alternative media distribution for musical pieces. This research is in Makassar, on indie musicians who using Soundcloud. As for the method of this research used Descriptive Qualitative. The result of this research shows that indie musicians in Makassar have different motives on using Soundcloud as an alternative media distribution. The first, musicians used soundcloud to promote their works. The second, as an effort to distribute their works through the download feature. The third, Soundcloud is unsophisticated and very friendly media. The fourth, Soundcloud is utilized by musicians for the sake of protection feature for their uploaded works. The fifth, musicians used Soundcloud as a means of documentation for their works. The variety of Soundcloud uses been applied by indie musicians. The musician effort to utilize the feature not just confined by uploaded the works. Makassar indie musicians also integrated their Soundcloud account to another social media. Furthermore, they are providing download feature for their listeners, so they can download it for free. However, no musicians yet utilized description feature to describe the music context of their works.